System reliability analysis considering fatal and non-fatal shocks in a fault tolerant system - Liudong Xing; Boddu, P.; Yan Sun (2009 Annual Reliability and Maintainability Symposium, 2009)
Systems designed with fault-tolerance techniques are typically subject to common-cause shocks. Failure to consider common-cause shocks in the system reliability analysis leads to optimistic results, which makes the reliability analysis less effective in the system design and turning activities. In this paper, we consider two types of common-cause shocks: fatal and non-fatal in the reliability evaluation of fault-tolerant systems. A fatal shock will fail all components of a system, while a non-fatal shock causes the affected components to fail with different probabilities. Hierarchical combinatorial approaches and a Markov approach have been proposed for incorporating common-cause shocks in the reliability analysis of static and dynamic systems, respectively. The basics of the proposed approaches and effects of common-cause shocks on the system reliability are illustrated through examples.